The Effect of Student Team Achievement (STAD) Cooperative Learning Model on the Fourth-Grade Students’ Learning Outcomes at Assisi Medan Elementary School - Saskia Kristina; Bogor Lumbanraja; Patri Janson Silaban; Rumiris Lumban Gaol; Juliana Juliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the effect of applying the Student Team Achievement Division (STAD) cooperative learning model on student learning outcomes on the theme of the area where I live in class IV of SD Assisi Medan in the academic year 2022/2023. The research uses quantitative methods. The research population involves 180 fourth-grade students at SD Assisi Medan. The sampling used simple random sampling and the sample used was 44 fourth-grade students. The research results indicate that students’ learning outcomes using the Student Team Achievement Division (STAD) cooperative learning model are in the very good category with an average score of 83.48. The correlation test result is 0.958, which means rcount (0.958) ≥ rtable (0.297), so that Ha is accepted. Thus, there is a significant effect between the use of the Student Team Achievement Division (STAD) cooperative learning model on students’ learning outcomes on the theme of the area where I live in class IV of SD Assisi Medan. It can be seen from the results of the T-test research where tcount 21,720 ≥ ttable 2,015 so it can be stated that Ha is accepted. It indicates that there is a significant positive effect from the use of the Student Team Achievement Division (STAD) cooperative learning model on students’ learning outcomes on the theme of the area where I live in class IV of SD Assisi Medan in the academic year 2022/2023.